Layanan Urun Dana Shariah (Sharia Equity Crowdfunding) Bagi Umkm, Mana Yang Harus Jadi Prioritas? - Atika Rukminastiti Masrifah (ITB AAS INDONESIA Surakarta, 2021)
Equity crowdfunding has emerged as one of many alternative financing options chosen by start-ups that cannot be financed by banks. There have been numerous studies conducted on equity crowdfunding. However, there have been few studies on Sharia equity crowdfunding. This research is expected to provide start-ups with the priorities they need to pursue in the use of Sharia equity crowdfunding, analyze their problems, and develop authority strategies to develop Sharia equity crowdfunding in Indonesia using the Interpretative Structural Modeling (ISM) approach. According to the findings of the study, information disclosure is still regarded as a critical issue in the development of Sharia equity crowdfunding. The main strategy for developing Sharia equity crowdfunding is the existence of regulations as a foundation for community protection and security, as well as Sharia aspects such as Sharia declarations, contractual aspects, Sharia issuers, Sharia stock instruments, Sharia banks as transaction intermediaries, and the Sharia Supervisory Board, which thoroughly oversees and evaluates them. Furthermore, Sharia equity crowdfunding is highly recommended as a financing solution for start-ups. As a result, it was deemed critical for this study to create a Sharia equity crowdfunding model as a form of advanced acceleration to provide new budgeting for a start-up, which then graduates to a sustainable business.